2010
DOI: 10.1177/105382590903200310
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Method Approach to Understanding Empowerment Processes and Outcomes of Adventure Education Program Experiences

Abstract: Although most providers of adventure education experiences would likely agree that the adventure education process can be "empowering," empirical examination of empowerment is relatively limited in the literature (Angell, 1994;Autry, 2001;Sklar & Gibson, 2004).While theories of empowerment (both processes and outcomes) have been advanced, the context in which empowerment is developed and acted upon, must also be understood (Narayan, 2005;Spreitzer & Doneson, 2005;Zimmerman, 1995). Thus, understanding how parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Empowerment. The Psychological Empowerment Scale (PES) is a 12-item scale based on the original questionnaire developed by Spreitzer 36 and then modified by Shellman 37 to measure participants' psychological empowerment. The PES displays acceptable levels of reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…Empowerment. The Psychological Empowerment Scale (PES) is a 12-item scale based on the original questionnaire developed by Spreitzer 36 and then modified by Shellman 37 to measure participants' psychological empowerment. The PES displays acceptable levels of reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, while it seems that not all courses are effective, as found by Hattie et al (1997), there is a growing body of literature suggesting that participants are reasonably likely to report positive personal outcomes from adventure programs (Shellman & Ewert, 2010), not just immediately after the course but also months or years later. Apart from improving scientific rigor (Ewert & Sibthorp, 2008), the challenges now include the documentation of observed (rather than self-reported) changes in participants, and description of the breadth of changes that might be experienced, rather than relying on measuring changes in researcher-determined, a priori outcomes (Lobato, 2006).…”
Section: Evaluations Of Adventure Education and Outdoor Management Trmentioning
confidence: 97%
“…A multitude of positive outcomes have been attributed to adventure programs. Improvements have been found in self‐concept and attitude (Beames, ; Cook, ; Draper et al., ; Ewert & Yoshino, ; Gillespie & Allen‐Craig, ; Hattie et al., ; Neill & Dias, ; Schell, Cotton, & Luxmoore, ; Shellman & Ewert, ; Wang, Liu, & Kahlid, ). Participants have also demonstrated skill development, especially with regard to communication, leadership, and teamwork (Hattie et al., ; Wang et al., ; Whittington & Mack, ).…”
Section: How Successful Are Adventure Programs?mentioning
confidence: 99%
“…Shellman and Ewert () concluded that it was the sense of achievement participants felt during a U.S. OB program that led to an increase in their psychological empowerment. This appears to come from being challenged, or, as explained by Luckner and Nadler (), being required to push past the “comfort zone” to a “groan zone” (p. 20).…”
Section: The Critical Programmatic Experiencesmentioning
confidence: 99%
See 1 more Smart Citation